Niobium-based negative electrode material and preparation method and application thereof
By coating the phosphate or solid electrolyte material of the titanium niobate negative electrode material, the problem of side reaction of niobium-based negative electrode material at high temperature is solved, its electrochemical performance and cycle stability are improved, and it is suitable for future solid-state battery technology.
Patent Information
- Application Number
- CN202411441873.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Niobium-based anode materials have surface side reaction problems at high magnification and high temperatures, and need to adapt to the future development of solid-state battery technology and require surface modification.
A phosphate material or solid electrolyte material coated with a matrix of titanium niobate negative electrode material is prepared by sintering and grinding to form a clad layer of 0.5%-15% mass percentage to improve the surface stability and ionic conductivity of the material.
It significantly reduces side reactions, improves the electrochemical performance and cyclic stability of the material, enhances the diffusion rate of lithium ions, prevents the decomposition of the electrolyte and surface reaction, and extends the life of the material.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a niobium-based negative electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion secondary batteries have the advantages of high operating voltage, light weight, no memory effect, low self-discharge rate, long cycle life, and high energy density. They are currently widely used in mobile phones, computers, electric vehicles and other fields. In recent years, due to environmental protection considerations, electric vehicles have been rapidly developed under the promotion of governments and automobile manufacturers, and lithium-ion secondary batteries have become the ideal power source for the new generation of electric vehicles with their excellent performance. At present, the positive electrode materials of lithium-ion secondary batteries that people are concerned about can be roughly divided into layered materials (represented by LiCoO2), olivine materials (represented by LiFePO4) and spinel structure materials (represented by LiMn2O4), and the negative electrode is graphite (C).
[0003] Although lithium batteries were successfully commercialized as early as 1991, with the increasing popularity of new energy vehicles, people have higher requirements for the convenience of batteries. How to ensure that future negative electrode materials can meet the above needs is crucial to the development of the new energy vehicle industry and the energy storage industry.
[0004] The discharge voltage of niobium-based negative electrode is about 1.6V, and it does not produce lithium dendrites. The theoretical discharge capacity is >360mAh / g, which is almost twice that of lithium titanate. It also has excellent fast charging performance and is the next generation of negative electrode material that has attracted much attention. However, the material still faces the problem of side reactions on the surface at high rates and high temperatures. In order to adapt to the development of future solid-state battery technology, the surface of the material also needs to be further modified.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The first object of the present application is to provide a niobium-based negative electrode material, characterized in that it comprises a titanium niobate negative electrode material matrix and a phosphate material or a solid electrolyte material coated on the surface of the titanium niobate negative electrode material matrix, and the chemical composition of the titanium niobate negative electrode material matrix is: M c Nb d O e ; Among them, 0<c≤1, 0<d≤1, 0<e≤1, and M is at least one of Na, K, Al, Mg, Zn, Ni, Mn, Fe, Co, Ti, Y, Sc, Ru, Cu, Mo, Ge, W, Zr, Ca, Nb, Ta, P, V, S, F, B, Si, Ba, Pb, In, Ga, Sb, Si, Bi and Sr.
[0007] Furthermore, the titanium niobate negative electrode material matrix has any of the following molecular formulas: Ni 0.166 Nb 0.333 O (NiNb2O6), Ti 0.142 Nb 0.286 O (TiNb2O7), Ti 0.069 Nb 0.345 O(Ti2Ni 10 O 29 )、Mg 0.023 Nb 0.391 O(Mg2Nb 34 O 87 )、Zn 0.023 Nb 0.391 O(Zn2Nb 34 O 87 )、Mo 0.030 Nb 0.364 O(MoNb 12 O 33 )、Ga 0.008 Nb 0.395 O(GaNb 49 O 124 )、Zr 0.16 1Nb 0.387 (ZrNb 24 O 62 ) and Ti 0.032 Nb 0.387 O(Ti2Nb 24 O 62 ) and their doped and coated derivatives.
[0008] Furthermore, the phosphate material is Al x M y (PO4)3,Cu x M y (PO4) 3z , Ti x M y (PO4) 3z , Zr x M y (PO4) 3z , Li x M y (PO4) 3z At least one of; Wherein 0<X≤3.3, 0≤y≤2.2, 0.2≤z≤1.1, M is at least one of Li, Na, Al, Mg, Zn, Ni, Mn, Fe, Co, Y, Sc, Ru, Cu, Mo, Ge, Ga, W, Zr, Ca, Nb, Ta, P, B, Si, Ba, Ti, Cr, Mo, Cd, Ag, Sn, Pb, S, Br, I, F or Sr, and when M is two or more elements, for any element in M, the subscripts in the chemical formula of the phosphate material respectively satisfy the value range of y.
[0009] Furthermore, the chemical formula of the solid electrolyte material is Li 7-y La x A 3-x Zr 2-y M y O 12 , a composite metal oxide having a garnet-type crystal structure represented by, wherein in the above chemical formula, A is any metal selected from the group consisting of yttrium, neodymium, samarium, and gadolinium, wherein 0<X≤3.3, 0≤y≤2.2, or the chemical formula is Li 1+x+y (Al,Ga) x (Ti,Ge) 2-x Si y P 3-y O 12 , wherein 0<X≤3.3, 0≤y≤2.2, represents a composite metal oxide having a superionic conductor type crystal structure.
[0010] Furthermore, the coating material is at least one of a phosphate material and a solid electrolyte material, and the mass of the phosphate material and the solid electrolyte material is calculated in percentage by mass, and the mass of the coating layer is 0.5%-15% of the mass of the niobium-based negative electrode material matrix.
[0011] Furthermore, the particle size D50 of the niobium-based negative electrode material matrix ranges from 50nm to 20um; The particle size D50 of the coating material is 2nm-10um.
[0012] The second object of the present application is to provide a method for preparing a niobium-based negative electrode material, characterized in that the method is used to prepare the above-mentioned niobium-based negative electrode material, comprising the following steps: Step 1: Mixing, sintering, crushing, screening and demagnetizing the metal source and the niobium source to obtain a niobate matrix; Step 2: Grinding and mixing the niobium-based negative electrode material and the phosphate material or the phosphate material matrix or the solid electrolyte material or the solid electrolyte material matrix; Step 3: Sintering the mixed material, crushing, screening and demagnetizing the sintered material to obtain a niobium-based negative electrode material.
[0013] Furthermore, the phosphate material or the solid electrolyte material is synthesized by uniformly mixing a single substance or a compound containing the phosphate material and the solid electrolyte material, wherein the single substance or the compound containing the phosphate material and the solid electrolyte material is a matrix of the phosphate material or the solid electrolyte material.
[0014] The third object of the present application is to provide a lithium battery negative electrode, comprising the above-mentioned niobium-based negative electrode material.
[0015] The fourth objective of the present application is to provide a lithium battery, the negative electrode of the lithium battery being loaded with the above-mentioned negative electrode of the lithium battery.
[0016] By adopting the above technical solution, the present invention has the following beneficial effects: 1. When the coating material is phosphate such as Li3PO4, LiTi2(PO4)3, aluminum phosphate, etc., it has the function of protecting the surface of niobium-based negative electrode materials, making the surface of niobium-based negative electrode more resistant to high pressure and the formed SEI more stable.
[0017] 2. When the coating material is solid electrolyte material is Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li7La3Zr2O 12 When solid electrolytes are used, the ionic conductivity of solid electrolytes can be greatly improved, and the diffusion rate of lithium ions can be increased, thereby reducing polarization and reducing surface side reactions. DETAILED DESCRIPTION
[0018] The embodiment of the present application provides a niobium-based negative electrode material, characterized in that it includes a titanium niobate negative electrode material matrix and a phosphate material or a solid electrolyte material coated on the surface of the titanium niobate negative electrode material matrix, the phosphate material or the solid electrolyte material is a coating material, and after being coated on the surface of the titanium niobate negative electrode material matrix, it is a coating layer, and the chemical composition of the titanium niobate negative electrode material matrix is: M c Nb d O e ; Among them, 0<c≤1, 0<d≤1, 0<e≤1, and M is at least one of Na, K, Al, Mg, Zn, Ni, Mn, Fe, Co, Ti, Y, Sc, Ru, Cu, Mo, Ge, W, Zr, Ca, Nb, Ta, P, V, S, F, B, Si, Ba, Pb, In, Ga, Sb, Si, Bi and Sr.
[0019] It should be noted that although the niobium-based negative electrode has good cycle performance at room temperature, it will still react with the electrolyte at high temperature, and then an interfacial film will be formed at the interface, which will not only lead to performance degradation, but also slow down the interfacial lithium ion transmission. Through a lot of research and experiments, different substances are tested adjacent to or coated on the surface of niobium-based negative electrode materials, and the following conclusions are obtained: During the experiment, phosphate or solid electrolyte material was used adjacent to or coated on the surface of niobium-based negative electrode material. When phosphate Li3PO4 and LiTi2(PO4)3 were used, the surface stability of niobium-based material was significantly increased, the side reaction of niobium-based negative electrode material was reduced, and the structure was stabilized. When solid electrolyte material was used as Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li7La3Zr2O 12 It can greatly improve the ionic conductivity of the surface of the negative electrode material, while reducing the side reactions on the surface of the negative electrode material. From the mechanism point of view, it can be further shown that the adjacent or coated material increases the stability of the solid electrolyte film on the surface of the niobium-based negative electrode, thereby improving the electrochemical performance of the material. By arranging a solid electrolyte material adjacent to or coated with the niobium-based negative electrode material, it can effectively prevent the material from direct contact with the electrolyte, inhibit the decomposition of the electrolyte at high temperature and the occurrence of surface side reactions, improve the stability of the material surface structure, and improve the cycle.
[0020] The titanium niobate negative electrode material matrix has any of the following molecular formulas: Ni 0.166 Nb 0.333 O (NiNb2O6), Ti 0.142 Nb 0.286 O (TiNb2O7), Ti 0.069 Nb 0.345 O(Ti2Ni 10 O 29 )、Mg 0.023 Nb 0.391 O(Mg2Nb 34 O 87 )、Zn 0.023 Nb 0.391 O(Zn2Nb 34 O 87 )、Mo 0.030 Nb 0.364 O(MoNb 12 O 33 )、Ga 0.008 Nb 0.395 O(GaNb 49 O 124 )、Zr 0.16 1Nb 0.387 (ZrNb 24 O62 ) and Ti 0.032 Nb 0.387 O(Ti2Nb 24 O 62 ) and their doped and coated derivatives.
[0021] The coating material is phosphate and solid electrolyte material.
[0022] In some possible embodiments, the adjacent or coated phosphate material or solid electrolyte material is Al(PO4)3, LiTi2(PO4)3, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 or Li7La3Zr2O 12 At least one of LiCoPO4, LiTi2(PO4)3, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 or Li7La3Zr2O 12 In the process of modifying niobium-based negative electrode materials, the elements in the niobium-based negative electrode materials may be partially doped into Al(PO4)3, LiTi2(PO4)3, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 or Li7La3Zr2O 12 Sometimes, adjacent or encapsulating materials such as LiCoPO4, LiTi2(PO4)3, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 or Li7La3Zr2O 12 During the synthesis process, trace amounts of other metal and non-metal substances are added to adjacent or coated materials such as LiTi2(PO4)3 and Li 1.3 Al 0.3 Ti 1.7 (PO4)3 or Li7La3Zr2O 12 After further coating and doping, the phosphate material or solid electrolyte material obtained by this modification still has the same properties as LiTi2(PO4)3, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 or Li7La3Zr2O 12 The same material structure, the above-mentioned use of doped and modified LiTi2(PO4)3, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 or Li7La3Zr2O 12Phosphate materials or solid electrolyte materials also fall within the protection scope of this patent.
[0023] In some possible embodiments, the median particle size D50 of the coating material matrix can be 500nm, 2um, 4um, the thickness of the coating is 2nm-5um, the thickness of the coating is 100nm-15um, the thickness of the coating can be 200nm, 600nm, 1μm, 5μm or 10μm.
[0024] The coating layer is evenly distributed on the surface of the niobium-based negative electrode material, and the coating layer can also be distributed in island shapes on the surface of the niobium-based negative electrode material.
[0025] In some possible embodiments, the median particle size of the adjacent coating material is similar to the median particle size of the niobium-based negative electrode material. In the embodiment of the present application, the particle size of the niobium-based negative electrode material is 10nm-20μm, preferably, the particle size of the niobium-based negative electrode material is 1μm-17μm. Exemplarily, the particle size of the base material is 2μm, 4μm, 6μm, 8μm or 10μm.
[0026] In the comparative example of the present application, the base material is a niobium-based material, and the chemical composition is: M c Nb d O e , wherein 0<c≤1, 0<d≤1, 0<e≤1, and M is at least one of Na, K, Al, Mg, Zn, Ni, Mn, Fe, Co, Ti, Y, Sc, Ru, Cu, Mo, Ge, W, Zr, Ca, Nb, Ta, P, V, S, F, B, Si, Ba, Pb, In, Ga, Sb, Si, Bi and Sr.
[0027] The titanium niobate negative electrode material matrix has any of the following molecular formulas: Ni 0.166 Nb 0.333 O (NiNb2O6), Ti 0.142 Nb 0.286 O (TiNb2O7), Ti 0.069 Nb 0.345 O(Ti2Ni 10 O 29 )、Mg 0.023 Nb 0.391 O(Mg2Nb 34 O 87 )、Zn 0.023 Nb 0.391 O(Zn2Nb 34 O 87 )、Mo 0.030 Nb 0.364 O(MoNb 12 O 33 )、Ga0.008 Nb 0.395 O(GaNb 49 O 124 )、Zr 0.16 1Nb 0.387 (ZrNb 24 O 62 ) and Ti 0.032 Nb 0.387 O(Ti2Nb 24 O 62 ) and their doped and coated derivatives.
[0028] Phosphate material is Al x M y (PO4)3,Cu x M y (PO4) 3z , Ti x M y (PO4) 3z , Zr x M y (PO4) 3z , Li x M y (PO4) 3z At least one of; Wherein 0<X≤3.3, 0≤y≤2.2, 0.2≤z≤1.1, M is at least one of Li, Na, Al, Mg, Zn, Ni, Mn, Fe, Co, Y, Sc, Ru, Cu, Mo, Ge, Ga, W, Zr, Ca, Nb, Ta, P, B, Si, Ba, Ti, Cr, Mo, Cd, Ag, Sn, Pb, S, Br, I, F or Sr, and when M is two or more elements, for any element in M, the subscripts in the chemical formula of the phosphate material respectively satisfy the value range of y.
[0029] The chemical formula of the solid electrolyte material is Li 7-y La x A 3-x Zr 2-y M y O 12 , a composite metal oxide having a garnet-type crystal structure represented by, wherein in the above chemical formula, A is any metal selected from the group consisting of yttrium, neodymium, samarium, and gadolinium, wherein 0<X≤3.3, 0≤y≤2.2, or the chemical formula is Li 1+x+y (Al,Ga) x (Ti,Ge) 2-x Si y P 3-y O 12, wherein 0<X≤3.3, 0≤y≤2.2, represents a composite metal oxide having a superionic conductor type crystal structure.
[0030] The coating material is at least one of a phosphate material and a solid electrolyte material. The coating material may also be Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li7La3Zr2O 12 At least one of the phosphate material and the solid electrolyte material is calculated by mass percentage, and the mass of the coating layer is 0.5%-15% of the mass of the niobium-based negative electrode material matrix.
[0031] The particle size D50 of the niobium-based negative electrode material matrix ranges from 50nm to 20um; The particle size D50 of the coating material is 2nm-10um, and the thickness is 2nm-10um. The median particle size of the coating material is similar to that of the niobium-based negative electrode material. When the coating material is coated on the surface of the niobium-based negative electrode material, the lithium-ion battery material also includes a transition layer, which is formed between the coating material and the coated material. The composition and structure of the transition layer are between the coating material and the coated material. By forming a transition layer between the niobium-based negative electrode material and the coating layer, the tightness of the connection between the core and the coating layer can be improved, so that the coating layer is not easy to fall off, and the entire material is more stable.
[0032] The present application also provides a method for preparing a niobium-based negative electrode material, which is characterized in that the method for preparing the above-mentioned niobium-based negative electrode material comprises the following steps: Step 1: Mixing, sintering, crushing, screening and demagnetizing the metal source and the niobium source to obtain a niobate matrix, wherein the niobium source is one or more of niobium pentoxide, niobium oxide, niobium chloride, niobium oxalate, ammonium niobium oxalate, niobium dioxide and metallic niobium, the median particle size D50 of the niobium-based negative electrode material is 50nm-20μm, and the median particle size D50 of the phosphate material or the solid electrolyte material is 2nm-5μm. During sintering, the temperature is 100°C-1400°C, and the sintering time is 1h-30h; Step 2: Grinding and mixing the niobium-based negative electrode material and the phosphate material or the phosphate material matrix or the solid electrolyte material or the solid electrolyte material matrix; Step 3: Sintering the mixed material, crushing, screening and demagnetizing the sintered material to obtain a niobium-based negative electrode material.
[0033] The phosphate material or solid electrolyte material is synthesized by uniformly mixing a single substance or compound containing the phosphate material and the solid electrolyte material, wherein the single substance or compound containing the phosphate material and the solid electrolyte material is a matrix of the phosphate material or the solid electrolyte material.
[0034] An embodiment of the present application also provides a lithium battery negative electrode, comprising the above-mentioned niobium-based negative electrode material.
[0035] The embodiments of the present application further provide a lithium-ion battery slurry, wherein the slurry contains lithium-ion battery active materials, and the lithium-ion battery active materials include the above-mentioned lithium-ion battery materials.
[0036] An embodiment of the present application further provides a lithium battery, the negative electrode of the lithium battery being loaded with the above-mentioned negative electrode of the lithium battery.
[0037] In some possible implementations, a method for preparing a niobium-based negative electrode material comprises the following steps: Step S1, preparing a niobium-based negative electrode matrix material, mixing the raw materials for preparing the niobium-based negative electrode uniformly, and calcining, the median particle size D50 of the niobium-based negative electrode material is 10nm-20μm, and the particle size of the niobium-based negative electrode material is 1μm-17μm; weighing 15.38g of niobium oxide and 4.52g of titanium dioxide material, mixing them uniformly, and sintering them at 1200 degrees Celsius for 12h to obtain a titanium niobate matrix negative electrode, and the median particle size D50 can be crushed into 100nm-20μm as needed; Step S2, preparing a coated niobium-based material, grinding the prepared coated niobium-based material to a preset particle size, wherein the median particle size D50 of the coating layer material is 2nm-20um; The niobium-based negative electrode matrix material prepared in step S1 and the phosphate or solid electrolyte coating material or coating material precursor are uniformly mixed and sintered at a high temperature.
[0038] Other niobium-based negative electrode materials can be prepared using conventional methods in the art.
[0039] The niobium-based negative electrode material prepared in step S1 and the coating material prepared in step S2 are sintered, including: heating to 300° C.-1300° C. at a heating rate of 0.5° C. / min-8° C. / min and sintering for 1 h-10 h.
[0040] Some embodiments of the present application provide a lithium-ion battery slurry, wherein the slurry comprises a lithium-ion battery active material, and the lithium-ion battery material is loaded on the lithium-ion battery active material.
[0041] Some embodiments of the present application provide a negative electrode plate, which includes a current collector, on which a negative electrode active material is loaded, or on which a positive electrode active material prepared by a method for preparing a niobium-based negative electrode material is loaded.
[0042] Some embodiments of the present application provide a lithium battery comprising the above-mentioned negative electrode plate.
[0043] In some possible embodiments, the lithium battery further includes at least two of a separator, an electrolyte, a positive electrode, and a lithium supplement, and the negative electrode active material provided above.
[0044] In the above-mentioned lithium battery, the electrolyte can be a commonly used liquid electrolyte or solid electrolyte, the liquid electrolyte can be composed of an organic solvent and a lithium salt, the organic solvent can be selected from one or more of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, butylene carbonate, ethylene sulfite, propylene sulfite, diethyl sulfite, γ-butyrolactone, dimethyl sulfoxide, ethyl acetate, methyl acetate, tetrahydrofuran, dimethylmethane, 2-dimethyltetrahydrofuran, 1,2-dimethylethane, 1,3-dioxolane and diethylene glycol dimethyl ether; the lithium salt can be selected from one or more of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium bistrifluoromethylsulfonyl imide, lithium trifluoromethylsulfonate, lithium difluorooxalatoborate and lithium bisoxalatoborate. The liquid electrolyte can also contain electrolyte additives of elements such as N, P, Si, B, F, S, or electrolyte additives containing carbonyl or benzene rings. The solid electrolyte can be Li 3 x La 2 / 3-x Perovskite of TiO3 (0≤x≤2 / 3); having the general formula Li x M y NaSICON of (PO4)3 (1≤x≤3, 1≤y≤2, M is selected from one or more of Ge, Al, Ti, Ga, Zr, Fe and Nb); ceramic oxides with garnet structure; sulfides composed of Li2S-P2S5 and Li2S-Ge2S5; and solid electrolytes with other crystalline or amorphous structures, such as Li3N, LISICON (Lithium Super Ionic Conductor), Thio-LISICON (Li 3.25 Ge 0.25 P 0.75 S4), LiPON, PEO and other oxide-based, sulfide-based, phosphate-based and polymer-based materials, wherein ceramic oxides with garnet structure such as oxide Li5La3M2O 12 (M=Nb or Ta), Li6ALa2M2O 12 (A=Ca, Sr or Ba; M=Nb or Ta), Li 5.5 3M 1.75 B 0.25 O 12 (M=Nb or Ta; B=In or Zr), Li7La3Zr2O 12 and Li 7.06 M3Y 0.06 Zr 1.94 O12 (M=La, Nb or Ta) When a solid electrolyte is used, the particle size of the solid electrolyte particles may be 0.1-20 μm, preferably 0.5-10 μm.
[0045] In the above-mentioned lithium batteries, the lithium supplement is a substance containing lithium, such as lithium powder, lithium strip, lithium rod, organic lithium, inorganic lithium, including but not limited to Li6CoO4, Li2NiO2, Li2S, Li5FeO4, LiF, Li2O, Li2O2, Li3N and other substances.
[0046] In the above-mentioned lithium battery, the positive electrode may include, for example, LiCoO2, LiMnO2, LiNiO2, LiVO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiMn2O4, Li(Ni 0.5 Mn 1.5 )O4, Li2FeSiO4, Li2MnSiO4, and doped and coated derivatives of the aforementioned positive electrode materials. In addition to the active materials disclosed in this patent, the negative electrode may also include an active material that can absorb and release lithium ions, such as graphite, Li metal, a metal that can form an alloy with Li metal, and a mixture or alloy thereof. As a metal that can form an alloy with Li (or referred to as an "alloying material"), it is preferably one or more of aluminum, silicon, tin, bismuth and indium.
[0047] The features and performance of the present application are further described in detail below in conjunction with the embodiments: Comparative Example 1: A conventional negative electrode active material is provided, which is prepared according to the following steps: 15.38 g of niobium oxide and 4.52 g of titanium dioxide material were weighed and uniformly mixed, and sintered at 1200 degrees Celsius for 12 hours to obtain sample 1 titanium niobate negative electrode.
[0048] Comparative Example 2: 26.6 g of niobium oxide and 9.27 g of nickel hydroxide material were uniformly mixed and sintered at 1100 degrees Celsius for 10 hours to obtain sample 2, NiNb2O6 negative electrode material.
[0049] Embodiment 1: A negative electrode active material is provided, which is prepared according to the following steps: 100 g of titanium niobate prepared in Comparative Example 1 and 2 g of lithium phosphate with a median particle size D50 of 10 nm were taken, and after grinding, crushing, dispersing and mixing, the above powders were placed in a box furnace and calcined at 600° C. for 7 hours to obtain Sample 3.
[0050] Embodiment 2: A negative electrode active material is provided, which is prepared according to the following steps: Take 100g of titanium niobate prepared in Comparative Example 1 and 3g of lithium aluminum titanium phosphate with a median particle size D50 of 20nm, grind, crush, disperse and mix, then place the ground powder in a box furnace and calcine at 800°C for 5h to finally obtain Sample 4.
[0051] Embodiment 3: Take 100g of titanium niobate prepared in Comparative Example 1 and 5g of lithium aluminum titanium phosphate with a median particle size D50 of 1um, put them into a mortar, grind for 60 minutes, then place the ground powder in a box furnace, calcine at 1000°C for 5 hours, and finally obtain sample 5.
[0052] Embodiment 4: Take 100g of titanium niobate prepared in Comparative Example 1 and 0.48g of lithium carbonate, 0.153g of aluminum oxide, 1.93g of titanium dioxide and 2.13g of phosphorus pentoxide, grind, crush, disperse and mix, then place the above powder in a box furnace, calcine at 900°C for 5h and 1050°C for 5h, and finally obtain Sample 6.
[0053] Embodiment 5: A positive electrode active material is provided, which is prepared according to the following steps: Take 100g of nickel niobate prepared in Comparative Example 2 and 3g of lithium lanthanum zirconium oxide with a median particle size D50 of 30nm, grind, crush, disperse and mix them, then place the ground powder in a box furnace and calcine at 800°C for 8h to finally obtain Sample 7.
[0054] The electrochemical performance tests of the negative electrode active materials of samples 1-7 were performed.
[0055] First, the negative electrode active materials prepared from samples 1-7 were prepared into button-type batteries according to the following method.
[0056] 1) Preparation of negative electrode sheet The negative electrode active material prepared from sample 1-7, carbon black as a conductive additive and polyvinylidene fluoride (PVDF) as a binder were dispersed in N-methylpyrrolidone (NMP) at a weight ratio of 80:10:10, mixed evenly, and prepared into a uniform positive electrode slurry. The uniform negative electrode slurry was evenly coated on an aluminum foil current collector with a thickness of 15 μm, dried at 55°C to form a pole piece with a thickness of 100 μm, and the pole piece was placed under a roller press (pressure of about 1 MPa×1.5 cm 2 ), cut into discs with a diameter of φ14mm, and then placed in a vacuum oven at 120℃ for 6h. After natural cooling, take out and place in a glove box for use as an electrode.
[0057] 2) Assembling lithium-ion secondary batteries In a glove box filled with an inert atmosphere, metallic lithium is used as the negative electrode of the battery, a three-layer film of PP / PE / PP coated with aluminum oxide on both sides is placed between the positive and negative electrodes as a separator, a commonly used carbonate electrolyte is added, and the electrode prepared in step 1) is used as the positive electrode to assemble a button battery of model CR2032.
[0058] Battery rate cycle performance test: After the button cell prepared above was left at room temperature (25°C) for 10 hours, the button cell was activated by charge and discharge, and then the button cell prepared above was tested for charge and discharge cycles using a Blue Power battery charge and discharge tester. The details are as follows: 1) At 55°C, the discharge capacity and coulombic efficiency of the button cells assembled with the negative electrode active materials of the test samples 1-7 were tested at a rate of 0.1C for 1 week and a rate of 1C for 99 weeks, as shown in Table 1:
[0059] From Table 1 above, it can be concluded that Comparative Examples 1 and 2 are uncoated materials, and after 100 cycles, the capacity decreases significantly; while Examples 1-5 are coated materials, and their high-temperature cycle performance is significantly better than that of Comparative Examples 1 and 2, and the efficiency is also higher. Therefore, the present application is conducive to improving interface stability and cycle stability.
[0060] Rate performance test The button cells prepared using the negative electrode active materials prepared from samples 1-7 were first activated at 25° C. at a rate of 0.05 C for three weeks and then discharged at a rate of 5 C. The results are shown in Table 2.
[0061] It can be concluded from Table 2 that the discharge capacity of the coated sample at room temperature is significantly improved. Therefore, the discharge capacity of the high dielectric constant material of the present application at room temperature is significantly improved.
[0062] This specific embodiment is merely an explanation of the invention and is not a limitation of the invention. After reading this specification, those skilled in the art may make non-creative modifications to this embodiment as needed. However, as long as they are within the scope of protection of the invention, they are protected by patent law.
Claims
1. A niobium-based negative electrode material, It is characterized in that It includes a titanium niobate negative electrode material matrix and a phosphate material or a solid electrolyte material coated on the surface of the titanium niobate negative electrode material matrix, and the chemical composition of the titanium niobate negative electrode material matrix is: c Nb d O e ; Among them, 0<c≤1, 0<d≤1, 0<e≤1, and M is at least one of Na, K, Al, Mg, Zn, Ni, Mn, Fe, Co, Ti, Y, Sc, Ru, Cu, Mo, Ge, W, Zr, Ca, Nb, Ta, P, V, S, F, B, Si, Ba, Pb, In, Ga, Sb, Si, Bi and Sr.
2. The niobium-based negative electrode material according to claim 1, It is characterized in that The titanium niobate negative electrode material matrix has any of the following molecular formulas: Ni 0.166 Nb 0.333 O(NiNb 2 O 6 )、Ti 0.142 Nb 0.286 O(TiNb 2 O 7 )、Ti 0.069 Nb 0.345 O(Ti 2 Ni 10 O 29 )、Mg 0.023 Nb 0.391 O(Mg 2 Nb 34 O 87 )、Zn 0.023 Nb 0.391 O(Zn 2 Nb 34 O 87 )、Mo 0.030 Nb 0.364 O(MoNb 12 O 33 )、Ga 0.008 Nb 0.395 O(GaNb 49 O 124 )、Zr 0.16 1Nb 0.387 (ZrNb 24 O 62 ) and Ti 0.032 Nb 0.387 O(Ti 2 Nb 24 O 62 ) and their doped and coated derivatives.
3. The niobium-based negative electrode material according to claim 2, It is characterized in that The phosphate material is Al x M y (PO 4 ) 3 , Cu x M y (PO 4 ) 3z , Ti x M y (PO 4 ) 3z , Zr x M y (PO 4 ) 3z , Li x M y (PO 4 ) 3z At least one of; Wherein 0<X≤3.3, 0≤y≤2.2, 0.2≤z≤1.1, M is at least one of Li, Na, Al, Mg, Zn, Ni, Mn, Fe, Co, Y, Sc, Ru, Cu, Mo, Ge, Ga, W, Zr, Ca, Nb, Ta, P, B, Si, Ba, Ti, Cr, Mo, Cd, Ag, Sn, Pb, S, Br, I, F or Sr, and when M is two or more elements, for any element in M, the subscripts in the chemical formula of the phosphate material respectively satisfy the value range of y.
4. The niobium-based negative electrode material according to claim 3, It is characterized in that The chemical formula of the solid electrolyte material is Li 7-y La x A 3-x Zr 2-y M y O 12 , a composite metal oxide having a garnet-type crystal structure represented by, wherein in the above chemical formula, A is any metal selected from the group consisting of yttrium, neodymium, samarium, and gadolinium, wherein 0<X≤3.3, 0≤y≤2.2, or the chemical formula is Li 1+x+y (Al,Ga) x (Ti,Ge) 2-x Si y P 3-y O 12 , wherein 0<X≤3.3, 0≤y≤2.2, represents a composite metal oxide having a superionic conductor type crystal structure.
5. The niobium-based negative electrode material according to claim 4, It is characterized in that The coating material is at least one of a phosphate material and a solid electrolyte material. The phosphate material and the solid electrolyte material are expressed in percentage by mass, and the mass of the coating layer is 0.5%-15% of the mass of the niobium-based negative electrode material matrix.
6. The niobium-based negative electrode material according to claim 5, It is characterized in that The particle size D50 of the niobium-based negative electrode material matrix ranges from 50nm to 20um; The particle size D50 of the coating material is 2nm-10um.
7. A method for preparing a niobium-based negative electrode material, It is characterized in that The method for preparing the niobium-based negative electrode material according to any one of claims 1 to 6 comprises the following steps: Step 1: Mixing, sintering, crushing, screening and demagnetizing the metal source and the niobium source to obtain a niobate matrix; Step 2: Grinding and mixing the niobium-based negative electrode material and the phosphate material or the phosphate material matrix or the solid electrolyte material or the solid electrolyte material matrix; Step 3: Sintering the mixed material, crushing, screening and demagnetizing the sintered material to obtain a niobium-based negative electrode material.
8. The method for preparing a niobium-based negative electrode material according to claim 7, It is characterized in that The phosphate material or solid electrolyte material is synthesized by uniformly mixing a single substance or compound containing a phosphate material and a solid electrolyte material, wherein the single substance or compound containing the phosphate material and the solid electrolyte material is a matrix of the phosphate material or the solid electrolyte material.
9. A lithium battery negative electrode, It is characterized in that The invention comprises the niobium-based negative electrode material as described in any one of claims 1 to 8.
10. A lithium battery, It is characterized in that The negative electrode of the lithium battery is loaded with the negative electrode of the lithium battery according to claim 9.
Citation Information
Patent Citations
Lithium ion battery negative pole active material and preparation method thereof, and lithium ion battery
CN103904305A
Lithium battery negative electrode material and preparation method thereof
CN114005967A
Negative electrode composite material and application thereof
CN114730883A
Preparation method of coated lithium aluminum titanium phosphate-based composite solid electrolyte
CN115642298A
Lithium ion battery and preparation method thereof
CN117239211A
